Penerapan Metode Pembelajaran Permainan Edukatif Terhadap Hasil Belajar IPA di SDN Sungai Miai 7 Banjarmasin - Nana Citrawati Lestari; Yulianti Hidayah; Fathul Zannah (Departement of Mathematics Education, 2023)
The use of various learning methods is naturally carried out by teachers as educators. Learning science in elementary schools requires the use of interesting learning methods to have a positive impact on learning outcomes. One of the learning methods that can be used by teachers for science learning is the educational game method. Several studies using the game method in learning activities show satisfactory results. However, very few studies with the title application of educational games to elementary science learning are found on the Google Scholar search page. Therefore researchers are interested in conducting research with the title